Matrix generalizations of integrable systems with Lax integro-differential representations - Sydorenko, Yu.M.; Chvartatskyi, O.I. (Carpathian Mathematical Publications, 2012)
We found matrix integro-differential Lax representations for Davey-Stewartson systems (DS-I, DS-II, DS-III), (2+1)-dimensional generalizations of Chen-Lee-Liu equation and its higher symmetries. In particular, we obtain (2+1)-dimensional generalizations of modified Korteweg-de Vries equation, Nizhnik equation and so etc. We also propose some matrix multidimensional generalizations of Burgers equation.